IMPLEMENTASI LESSON STUDY PADA PROSES PEMBELAJARAN KAJIAN PROSA FIKSI MAHASISWA SEMESTER III STKIP MUHAMMADIYAH KOTABUMI TAHUN AKADEMIK 2017/2018 - Sri Widayati (Universitas Muhammadiyah Kotabumi, 2018)
Implementation of Lesson Study in the third semester students of Indonesian Language and Literature Study Program STKIP Muhammadiyah Kotabumi academic year 2017/2018. The aims of this article is to improve the process of studying of fiction Prose. The undertaken activities are the activities of the Lesson Study team which are consisted of model lecturers and observers (observers). The lesson Study activities are conducted three times open class. Each open class consists of four stages of activity, namely: planning (plan), implementation (do), observation and reflection (see). Each planning stage produces a learning plan, an MFI, and an assessment instrument. The learning process was done through the application of cooperative learning strategies “cooperative learning model typed”. The results obtained from the implementation of lesson study, namely increasing the liveliness, creativity, and student independence. Students' understanding of the subject matter of fiction prose fiction was increased. The quality of learning also was increased.